Info Kampus UiTM Sarawak Isu 56 - Pariera, Halen; Ramli (Haji), Atikah (Universiti Teknologi MARA, Sarawak, 2007)
At first, i had mixed feelings about my recent appointment because i sensed the need for some changes to my personal lifestyle, many of which i know for certain i do not enjoy doing - thing like having to work on my weekends, being pompously dressed for the occasion and upholding some of the frills and formalities of the position.